2014
DOI: 10.1590/s0102-86502014000700008
|View full text |Cite
|
Sign up to set email alerts
|

Urethral dysfunction due to alloxan-induced diabetes. Urodynamic and morphological evaluation

Abstract: PURPOSE:To evaluate the effect of short and long term alloxan-induced diabetes on bladder and urethral function of female rats, and also describing its correlated morphological alterations. METHODS:Thirty five female rats were divided into three groups: G1 (n=9), control group; G2 (n=17), six weeks alloxan-induced diabetic rats; G3 (n=9), 20 weeks alloxan-induced diabetic rats. Functional evaluation was performed by cystometry and simultaneous measurements of the urethral pressure during bladder filling and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Acute surgically‐induced vesical denervation markedly increased BC and compliance in control and diabetic animals. A follow‐up study performed by the same group at 6 and 20 weeks after alloxan injection found no difference between control and diabetic animals for BC, voiding frequency or maximum pressure . Thus, except for the latter study, experiments in STZ‐injected mice and alloxan‐injected rats exhibited a similar cystometric profile as STZ‐injected rats.…”
Section: Exploration Of Links Between Hypertrophy and Bladder Dysfuncmentioning
confidence: 71%
See 3 more Smart Citations
“…Acute surgically‐induced vesical denervation markedly increased BC and compliance in control and diabetic animals. A follow‐up study performed by the same group at 6 and 20 weeks after alloxan injection found no difference between control and diabetic animals for BC, voiding frequency or maximum pressure . Thus, except for the latter study, experiments in STZ‐injected mice and alloxan‐injected rats exhibited a similar cystometric profile as STZ‐injected rats.…”
Section: Exploration Of Links Between Hypertrophy and Bladder Dysfuncmentioning
confidence: 71%
“…On the other hand, the two studies on alloxan‐injected rabbits also reported a modest degree of hypertrophy only based on BW (127‐133% of control) . Another possible difference is that there was little further bladder enlargement beyond week 1 in the rat STZ model, whereas one study in alloxan‐injected rats reported a bladder wall thickness of 553 μm in control and 655 μm in diabetic animals after 6 weeks, which increased further to 899 μm after 20 weeks . Therefore, the alloxan model confirms the existence of bladder hypertrophy in T1DM models but despite a similar extent of blood glucose elevation appears to cause less hypertrophy than injection of STZ.…”
Section: Comparison Of Hypertrophy Among Models Of Type 1 Diabetesmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies reported that the morphology of the urethra can also be altered in DM. For example, the urethras from 6 weeks and 20 weeks in alloxan-induced diabetic rats had greater values of total thickness than did the control rats whereas the urethra from 6- and 20-week DM rats had reduced thickness of the urothelium of the urethra [30]. In 6- and 20-week STZ-induced DM rats, the morphological images revealed that the striated muscle bundles in 20-week diabetic rats were atrophied compared with those of controls although no obvious changes were observed in the thickness of EUS of 6-week diabetic rats compared with controls (Fig.…”
Section: Preclinical Studymentioning
confidence: 99%